Volume increase in growth plate chondrocytes during hypertrophy: the contribution of organic osmolytes. - Farnum, C; Lee, R; O'Hara, K; Urban, J (2002)
During the differentiation cascade of growth plate chondrocytes, cells undergo as much as a 10-15-fold increase in volume. This volume increase, which occurs to different extents in growth plates growing at different rates, has been demonstrated to be the single most significant variable in understanding the quantitative aspects of the cellular kinetics of long bone growth. Our hypothesis is that this volume increase, which occurs through cell swelling by water imbibition, requires intracellular accumulation of osmolytes through activation or upregulation of membrane transport mechanisms. Significant intracellular accumulation of inorganic osmolytes, such as Na+, K+, and Cl-, is potentially disruptive to normal cellular metabolism, whereas intracellular accumulation of organic osmolytes is considered to be more compatible with metabolic function. Thus, we concentrated on determining the contributions of organic osmolytes--betaine, amino acids, inositol, and sorbitol--to volume increase. Pooled cryostat sections of young bovine growth plates were extracted followed by automated analysis for their content of amino acids. Analysis for betaine and the sugar alcohols was done by extraction and derivatization, followed by high-performance liquid chromatography (HPLC). Parallel stereological analyses correlated osmolyte changes to stages of chondrocytic differentiation, specifically comparing intracellular concentration and amount in proliferative vs. hypertrophic chondrocytes. Calculations demonstrated that, maximally, these organic osmolytes, in total, account for 6%-7% of the intracellular osmolytes required to sustain the volume increase, and that the most significant contribution is from betaine. This suggests that intracellular accumulation of organic osmolytes is not a primary strategy used by growth plate chondrocytes during volume increase of their terminal differentiation. The data also suggest that there is a differential regulation of transporters of these osmolytes such that intracellular concentrations are constantly modified as cells proceed through the differentiation cascade.